Vitreon, a Perfluorocarbon Liquid as Vitreous Substitute in Retinal Detachment Surgery - Tariq M Aziz, Faisal Murtaza, Alyscia Miryam Cheema, Javed Hassan Niazi, Imran Ghayoor (Pakistan Journal of Ophthalmology, 2009)
Purpose: To assess the role of perfluoroperhydrophenanthrene (vitreon) PFCL as an internal tamponade agent in complicated retinal detachment with regard to anatomical reattachment, visual outcome and complications. Material and Methods: This study was conducted in the Department of Ophthalmology J.P.M.C, Karachi, for 1 year, from July 2000 to June 2001, in 30 eyes of 30 patients. Patients with complicated retinal detachment who underwent three ports pars plana vitrectomy with vitreon (perfluoro-perhydro-phenanthrene) as an internal tamponade agent. Results: The mean age was 31.9 years. 7 patients were female (23.3%) and 23 were male (76.6%). 20 patients were phakic (66.6%), 3 patients were aphakic (23.3%) and 7 patients were pseudophakic. Eight patients were myopes (26.6%). Ten patients had retinal detachment with PVR Grade “C” in which break could not be localized preoperatively, 16 patients had inferior retinal detachment with posteriorly located breaks (53.3%), 1 patient had inferior tractional retinal detachment (3.3%) and 3 patients had retinal detachment associated with giant retinal tear (10%). Majority of patients had visual acuity up to counting fingers. 16 eyes (53.3%). Vitreon was used as an internal tamponading agent, which was later on replaced by silicone oil. Redetachemnt of retina due to PVR (26.6%) was the commonest postoperative complication. The overall anatomical success rate was (93.3%) and visual success rate was (63.3%). Conclusion: Vitreon can be safely tolerated by the eye and is a good intra oprative hydrokinetic tool to flatten the retina.